Czy reformacja w Polsce była luterańska? O polemikach antyluterańskich w Polsce w pierwszej połowie XVI wieku - Ptaszyński, Maciej (1978– ) (Instytut Historii PAN, 2019)
In the article the author discusses anti-Lutheran polemics published in the Kingdom of Poland during the rule of Sigismund I and asks about the shape of Reformation movement, which developed in spite of numerous bans imposed by the king. The author proves that although these polemics were explicitly against “Lutherans,” they were often created as a result of clashes with other theologies of the emerging Protestantism. Works created by the lower-status Church employees were not novel, and their range of influence must have been limited.
Summary in English. Abstract in English and Polish.
p. 5-62 ; illustrations
Keywords: Reformation - Poland 16th c.; Luther, Martin (1483-1546); Lutheran Church; Lutheranism; tolerance; polemics; religious tolerance - Poland 16th c.; Poland - Church history - 16th c.